The reproduction number in the classical epidemiological model - Georg Quaas (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2020)
The German Robert Koch Institute aims to "protect the population from disease and improve their state of health" (RKI 2017). To this end, it develops concrete, research-based recommendations for policymakers and makes data available to the expert public. Since March 4, 2020, it has been publishing the numbers of coronavirus infections reported by health authorities daily; since March 9, these data have included the numbers of people who have died of COVID-19; and since March 25, the RKI has reported the estimated numbers of those who have recovered. The important reproduction number, reported daily since April 7, has now largely replaced all other criteria used for decision-making. This paper aims to show that the calculation of this figure is neither theory-based nor particularly reliable. Nevertheless, there is a simple way to determine its change more or less conservatively and precisely.
Keywords: C32; C61; I12; I18; J11; 330; Classic epidemic model; reproduction number; contact rate; COVID-19; mathematics of highly infectious diseases; public health